A tissue engineered 3D printed calcium alkali phosphate bioceramic bone graft enables vascularization and regeneration of critical-size discontinuity bony defects in vivo - Knabe, Christine; Stiller, Michael; Kampschulte, Marian; Wilbig, Janka; Peleska, Barbara; Günster, Jens; Gildenhaar, Renate; Berger, Georg; Rack, Alexander; Linow, Ulf; Heiland, Max; Rendenbach, Carsten; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Recently, efforts towards the development of patient-specific 3D printed scaffolds for bone tissue engineering from bioactive ceramics have continuously intensified. For reconstruction of segmental defects after subtotal mandibulectomy a suitable tissue engineered bioceramic bone graft needs to be endowed with homogenously distributed osteoblasts in order to mimic the advantageous features of vascularized autologous fibula grafts, which represent the standard of care, contain osteogenic cells and are transplanted with the respective blood vessel. Consequently, inducing vascularization early on is pivotal for bone tissue engineering. The current study explored an advanced bone tissue engineering approach combining an advanced 3D printing technique for bioactive resorbable ceramic scaffolds with a perfusion cell culture technique for pre-colonization with mesenchymal stem cells, and with an intrinsic angiogenesis technique for regenerating critical size, segmental discontinuity defects in vivo applying a rat model. To this end, the effect of differing Si-CAOP (silica containing calcium alkali orthophosphate) scaffold microarchitecture arising from 3D powder bed printing (RP) or the Schwarzwalder Somers (SSM) replica fabrication technique on vascularization and bone regeneration was analyzed in vivo. In 80 rats 6-mm segmental discontinuity defects were created in the left femur. Embryonic mesenchymal stem cells were cultured on RP and SSM scaffolds for 7d under perfusion to create Si-CAOP grafts with terminally differentiated osteoblasts and mineralizing bone matrix. These scaffolds were implanted into the segmental defects in combination with an arteriovenous bundle (AVB). Native scaffolds without cells or AVB served as controls. After 3 and 6 months, femurs were processed for angio-µCT or hard tissue histology, histomorphometric and immunohistochemical analysis of angiogenic and osteogenic marker expression. At 3 and 6 months, defects reconstructed with RP scaffolds, cells and AVB displayed a statistically significant higher bone area fraction, blood vessel volume%, blood vessel surface/volume, blood vessel thickness, density and linear density than defects treated with the other scaffold configurations. Taken together, this study demonstrated that the AVB technique is well suited for inducing adequate vascularization of the tissue engineered scaffold graft in segmental defects after 3 and 6 months, and that our tissue engineering approach employing 3D powder bed printed scaffolds facilitated segmental defect repair.